2021
DOI: 10.1007/s10462-021-10048-6
|View full text |Cite|
|
Sign up to set email alerts
|

An approach to MCGDM based on multi-granulation Pythagorean fuzzy rough set over two universes and its application to medical decision problem

Abstract: Exploring efficiency approaches to solve the problems of decision making under uncertainty is a mainstream direction. This article explores the rough approximation of the uncertainty information with Pythagorean fuzzy information on multi-granularity space over two universes combined with grey relational analysis. Based on grey relational analysis, we present a new approach to calculate the relative degree or the attribute weight with Pythagorean fuzzy set and give a new descriptions for membership degree and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The first aspect is the background researches on three-way decisions. These researches mainly focus on the generalization of Pawlak's rough sets, such as decision-theoretic rough sets (Yao 2003(Yao , 2007(Yao , 2008, game-theoretic rough sets (Azam and Yao 2014), fuzzy rough sets/rough fuzzy sets (Dubois et al 1990), variable precision rough sets (Ziarko 1993), fuzzy covering-based rough sets (Yang and Hu 2016;Yang and Hu 2017), multi-granulation rough sets (Lin et al 2013;Sun et al 2021), and so on.…”
Section: A Short Review Of Three-way Decisionsmentioning
confidence: 99%
“…The first aspect is the background researches on three-way decisions. These researches mainly focus on the generalization of Pawlak's rough sets, such as decision-theoretic rough sets (Yao 2003(Yao , 2007(Yao , 2008, game-theoretic rough sets (Azam and Yao 2014), fuzzy rough sets/rough fuzzy sets (Dubois et al 1990), variable precision rough sets (Ziarko 1993), fuzzy covering-based rough sets (Yang and Hu 2016;Yang and Hu 2017), multi-granulation rough sets (Lin et al 2013;Sun et al 2021), and so on.…”
Section: A Short Review Of Three-way Decisionsmentioning
confidence: 99%
“…Further studies on MCDM with FSs and aggregation operators can be found in. 1,9,17,27,29,[39][40][41] As a generalization of IFS, the concept of Pythagorean fuzzy set (PFS) was developed by Yager, 33,34 which is defined by a membership function µ A : X → [0, 1] and a non-membership function ν A : X → [0, 1] under the condition µ 2 A (x) + ν 2 A (x) ≤ 1 for x ∈ X. A PFS is more capable than an IFS to express uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned theories are imperfectly designed to tackle MAGDM situations involving multiple decision‐makers simultaneously, see also Chen (2022); Naz et al (2022); Peng et al (2020); and Sun et al (2022). To account for simultaneous evaluations, Alkhazaleh and Salleh (2011) proposed the notion of soft expert (SE) sets.…”
Section: Introductionmentioning
confidence: 99%